2006
DOI: 10.1002/cyto.b.20135
|View full text |Cite
|
Sign up to set email alerts
|

An optimized whole blood method for flow cytometric measurement of ZAP‐70 protein expression in chronic lymphocytic leukemia

Abstract: Results: Using the optimized fixation and permeabilization method, improvement in assay performance (signal-to-noise, S/N) was seen in most of the antibodies tested. The custom SBZAP conjugate gave the best S/N when used in conjunction with this optimized fixation /permeabilization method. In conjunction with carefully standardized instrument set-up protocols, we obtained both intra-and interlaboratory reproducibility in the analysis of ZAP-70 expression in whole blood samples from normal and CLL patients.Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 29 publications
5
58
0
Order By: Relevance
“…The large subpopulation with high levels of ZAP-70 (median fluorescence ratio ¼ 45) most likely represents T lymphocytes, and the small subpopulation with the highest levels of the molecule (median fluorescence ratio ¼ 188) is consistent with the expression levels of NK cells. Although we did not specifically identify these subpopulations with multi-color staining, this interpretation conforms with the published results from other laboratories (16,21).…”
Section: Zap-70 Expression Among Peripheral Blood Mononuclear Cellssupporting
confidence: 90%
See 2 more Smart Citations
“…The large subpopulation with high levels of ZAP-70 (median fluorescence ratio ¼ 45) most likely represents T lymphocytes, and the small subpopulation with the highest levels of the molecule (median fluorescence ratio ¼ 188) is consistent with the expression levels of NK cells. Although we did not specifically identify these subpopulations with multi-color staining, this interpretation conforms with the published results from other laboratories (16,21).…”
Section: Zap-70 Expression Among Peripheral Blood Mononuclear Cellssupporting
confidence: 90%
“…demonstrated that phospho-ZAP-70, phospho-Syk, and p21 cip1 are stable in cells maintained at room temperature ex vivo for 24 hours (Table 3). It should be noted that others have shown that ZAP-70 levels decline over this period of time (15)(16)(17)(18)(19), but we have found they are relatively stable for 5 hours at room temperature, which is the time limit for processing in our procedure. Thus, the data we have obtained is reproducible, quantitative, stable upon freezing/thawing, and stable under the parameters of sample collection used in our procedure.…”
Section: Flow Cytometric Analysismentioning
confidence: 56%
See 1 more Smart Citation
“…Among proposed methods, calculating the ZAP70 T/B ratio is one of the earliest and most common approaches (12,(15)(16)(17)(18). Other methods based on ratios calculated on normal B-cell MFIs have drawbacks such as the very low percentage of residual B-cells or the difficulty of separating them from CLL cells by flow cytometry in the case of weak CD5 expression (11,13,32).…”
Section: T/b Ratio Does Not Reflect Zap70 Expression Levelsmentioning
confidence: 99%
“…Regarding the antibody and fluorochrome, various authors agree that the phycoerythrin-conjugated (PE-conjugated) SBZAP monoclonal antibody (mAb) is one of the best reagents for this method (11)(12)(13). Currently most groups express FCM results of ZAP70 expression in CLL B-cells as a ratio between mean fluorescence intensities (MFI) of ZAP70 in CLL B-cells and in normal residual or externally added B-cells (11,13,14) or, more frequently, as a ratio between ZAP70 MFIs in residual T-cells and CLL B-cells (ZAP70 T/ B ratio) (12,(15)(16)(17)(18)(19). The main disadvantage of the former method is that residual normal B-cells may be virtually absent in peripheral blood of patients with CLL and external addition of normal B-cells to the blood sample prior to staining supposes that ZAP70 levels in normal subjects are biologically stable.…”
Section: Introductionmentioning
confidence: 99%